Choosing optimal medium for cultivation of rich - Astaxanthin green microalga Haematococcus pluvialis - Hong, Dang Diem; Hoang, Dinh Duc; Thuy, Nguyen Thi; Lan Anh, Hoang Thi (Academia Journal of Biology, 2012)
Microalgae have a large biotechnology potential for production of a variety of compounds such as polysaccharides, lipids, proteins, carotenoids, pigments, vitamins, steroids. Recently, Haematococcus pluvialis has been widely studies as one of the best sources of ketocarotenoid pigment - astxanthin (3,3’-dihydroxy-b,b’-carotene-4,4’-dione), which holds high antioxidant activity approximately 10 times greater than other carotenoids, such as zeaxanthin, lutein, canthaxanthin and b-carotene, and over 500 times greater than a-tocopherol. For this reason, this alga is used for the pigmentation of cultured fish and shellfish, a food additive in the food industry, a superior antioxidant in the cosmetic industry, and an antiaging reagent as precusor of vitamin A, an anticancer agent through singlet oxygen quenching, and an immunomodulator in the pharmaceutical industry. Haematococcus pluvialis is unicellular fresh water microalga, green-colored, biflagellate, and motile in its vegetative stage. It belongs to Chlorophyta phylum, Chlorophyceae class, Volvocales order, Haematococcaceae family and Haematococcus genus. During the H. pluvialis life cycles, green vegetative cells mobile with two flagella grow both in the light and heterotrophically in the dark. Environmental stress induces encystment and morphological changes from motile vegetative cells to resting immotile aplanospores. When exposed to prolonged stress, H. pluvialis cell undergo enhanced carotenogenesis during the maturation of cyst cells. Astaxanthin could be accumulated up to 4-6% of dry cell weight. The massive accumulation of astaxanthin in cyst cell under light in extreme environmental condition (nutrient limitation, high light intensity, hight temperature, oxidative stress and salt stress) has been investigated by several authors. The techniques on H. pluvialis cultures for astxanthin production have been dramatically advanced in some countries. Currently, the use of two-stage processes for astaxanthin production has been fully reported. In this report, we have presented the effect of different culture media including C, modified BG-11, OHM and RM on the growth rate of H. pluvialis which was isolated from Hoa Binh province, Vietnam in different scales. Among four media, RM medium is the best for H. pluvialis cultivation expressed by maximal cell density (cells/ml): 50.74 ´ 104, 39 ´ 104, 144.90 ´ 104 and 38.3 ´ 104; chlorophyll a content (mg/l): 617.63, 743.82, 2010 and 689.06 and astaxanthin content (mg/l): 246.21, 399.15, 630 and 212.10; specific growth rate (m/day): 0.062, 0.192, 0.234 and 0.321, in 250 ml, 500 ml Erlenmeyer flask, 1.5 liter and 10 liter bottles, respectively after 30 days of cultivation. In cases of 1.5 and 10 liter bottles, dried weight was reached 4.92 and 1.86 g/l, respectively. In addition, the obtained results have indicated that cultivative process from test - tubes to 250 ml Erlenmeyer flasks with frequently in 2-4 days per time by supplementing 50% of refresh medium is necessary to maintain vegetative stage of cell for long time. In Vietnam, it is the first report on successful cultivation of green microalgae H. pluavialis - a potential source for astaxanthin which is a natural pigment used for food and pharmaceutical industries in the world in general and for salmon farming in particularly.